DIDACTIC ESCAPE ROOM, APPLIED AT UNIVERSITY, IN ONLINE TEACHING - VĂIDĂHĂZAN, Remus; JULEAN, Iulia; BARTHA, Velu-Sebastian (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2022)
The use of active teaching techniques combined with ludic aspects and game-based learning is a current field of investigation in higher education. The use of escape rooms is also being considered as an educational tool in many schools. Using a variety of scenarios and challenges, the escape rooms create an experience that is simultaneously motivational and educational for the participants (Manzano et al., 2021, p. 1). Our Didactic Escape Room was applied in the 2020-2021 academic year, at the end of the first semester, during the Covid-19 pandemic period, with online teaching, on a group of students from the Faculty of Physical Education and Sport (FEFS), enrolled at the psycho-pedagogical specialization within the Teacher Training Department, and on a group of students from the Faculty of Psychology and Educational Sciences, specializing in Pedagogy of Primary and Preschool Education (PIPP), within Babeș-Bolyai University, Cluj-Napoca. Through this intervention, we measured the general attractiveness, stimulation and novelty of a didactic Escape Room applied online, and we found that the degree of attractiveness for a didactic Escape Room, applied online, was high. Also, it was stimulating enough to generate engagement at the group level. We believe that the specificity of the group involved in the Escape Room is very important, and that each didactic activity of this kind be properly adapted for the class to which it is applied.